Modulation of Antioxidant Enzymes, Heat Shock Protein, and Intestinal Microbiota of Large Yellow Croaker (Larimichthys crocea) Under Acute Cold Stress - Lv, Huirong; Liu, Yanli; Li, Haidong; Yin, Xiaolong; Wang, Ping; Qu, Xiaoyu; Gao, Yang; Li, Weiye; Chu, Zhangjie (Frontiers in Marine Science, 2021)
The experiment was conducted in a sealed, temperature-controlled room. The initial water temperature of the treatment group was 12°C, lowered by 1°C a day to 8°C using a chiller, and maintained at that temperature for three days. The water temperature was then increased by 1°C per day to 12°C using a heater. The control group were the fish that kept at 12°C at the beginning of the experiment; T1 represents the group that sampled on the first day when the water temperature reached 8°C from 12°C; T2 represents the group that sampled when the fish had been kept at 8°C for three days; T3 represents the group sampled when the water temperature was increased to 12°C from 8°C. The antioxidant abilities of the liver, muscle, and intestine of large yellow croaker at different temperatures and times were determined, and the expression of HSP70 and HSP90 in the liver as well as the changes in intestinal microflora were investigated. The results showed that the activities of SOD, CAT, GSHPx, and MDA content increased significantly when the water temperature decreased from 12°C to 8°C, significantly higher than in the control group. The gene expression levels of HSP70 and HSP90 in the liver of large yellow croaker significantly increased under low temperature stress and were significantly higher than those in the control group. The diversity and abundance of intestinal microflora of large yellow croaker were altered when the water temperature was maintained at 8°C, although the change was not obvious. Proteobacteria, Firmicutes, and Bacteroidetes were the dominate phyla in both the 12°C and 8°C groups, and the temperature variation did not change the functional pathways of the microflora. In conclusion, the acute temperature variation affected the antioxidant ability and heat shock protein expression of large yellow croaker but did not affect the diversity or abundance of the intestinal microflora. These results will provide a theoretical basis for studying the mechanisms of large yellow croaker overwintering and adaptation to low temperatures.